Effect of aqueous extract of Mikania micrantha Kunth on seed germination and seedling growth of Cassia tora L. - Mishra, Kishor Kumar (Nepalese Journal of Biosciences, 2016)
The order of inhibitory effectiveness of various parts of Mikania micrantha on seed germination and seedling growth of Cassia tora was leaf >stem> inflorescence. The dry weight of C. tora seedlings was lowest under 25% concentration of leaf extract, and highest under treatment with 5% concentration of inflorescence extract of M. micrantha.